Distributed H∞ containment control of multiagent systems over switching topologies with communication time delay - Wang, Dong; Huang, Yun; Guo, Shixin; Wang, Wei (International journal of robust and nonlinear control, 2020)
Summary In this study, we consider the problem of distributed H∞ containment control for multiagent systems over switching communication topologies. There exists a constant time‐delay and the energy‐bounded communication disturbances in the information transmission process, which are considered. Using the relative output, we develop an observer‐based containment control scheme such that the followers asymptotically converge to the convex hull formed by the leaders with a guaranteed H∞ performance level. By constructing a Lyapunov functional and using the inequality technique, sufficient conditions for the existence of such dynamic controllers are obtained in terms of linear matrix inequalities. Finally, a numerical example is provided to demonstrate the effectiveness of the proposed control protocol.